The Role of Leaders in Driving Change and Innovation in The General Insurance Sector: A Literature Review and Future Research Directions - Pristiwanto Bani; Wahyuningsih Santoso (Green Publisher Indonesia, 2025)
This study examines the important role of leadership in driving change and innovation in the general insurance sector through a systematic literature review. By analyzing recent studies, we explore how leaders in the general insurance industry can effectively facilitate organizational transformation and foster a culture of innovation amid digital disruption and rapid market change. Through a systematic analysis of 43 scientific articles published between 2014-2024, the study identifies several key themes, namely visionary, adherent, and transformational leadership styles as catalysts for change, the importance of creating a culture of innovation, the use of technology and data analytics in product and service innovation, strategies for managing resistance to change, and developing organizational capabilities to innovate sustainably. We also examined the specific challenges insurance leaders face in managing change, such as technology disruptions, customer expectations, regulatory constraints and employee resistance. The findings show that leaders who successfully adopt a visionary, adaptive and transformational and human-centered leadership approach tend to be more effective in driving innovation and managing organizational change. The study provides insurance executives and policymakers with valuable insights into leadership strategies that can improve the competitiveness and sustainability of general insurers in the digital age. We also identify gaps in the existing literature and suggest directions for future research to better understand the dynamics of leadership in the context of innovation in the general insurance industry.